Africa's manufacturing puzzle: Evidence from Tanzanian and Ethiopian firms - Diao, Xinshen; Ellis, Mia; McMillan, Margaret S.; Rodrik, Dani (Oxford University Press, 2025)
Recent growth accelerations in Africa are characterized by declining shares of the labor force employed in agriculture, increasing labor productivity in agriculture, and declining labor productivity in modern sectors such as manufacturing. To shed light on this puzzle, this study disaggregates firms in the manufacturing sector by average size, using two newly created firm-level panels covering Tanzania (2008–2016) and Ethiopia (1996–2017). The analysis identifies a dichotomy between larger firms with superior productivity performance that do not expand employment and small firms that absorb employment but do not experience much productivity growth. Large, more productive firms use highly capital-intensive techniques, in line with global technology trends but significantly greater than what would be expected based on these countries’ income levels or relative factor endowments.